Optimum design of horizontal ground-coupled heat pump systems using spiral-coil-loop heat exchangers. (15th January 2016) - Go, Gyu-Hyun; Lee, Seung-Rae; Yoon, Seok; Kim, Min-Jun
Highlights: Optimum design of horizontal ground heat pump systems is presented. Accuracy of numerical model is verified through indoor thermal response tests. A total of 160 parametric studies are conducted using numerical simulation models. Heat efficiencies are compared for 160 major combinations of design factors. Optimum design conditions are suggested using several economic analysis tools. Abstract: This paper deals with an optimum design of horizontal ground heat pump systems for spiral-coil-loop heat exchangers. A three dimensional numerical analysis model simulating the thermal behavior of a horizontal spiral-coil-loop heat exchanger was developed, and the accuracy of the model was verified through indoor thermal response tests. After that, a total of 160 parametric studies were conducted using numerical simulation models in order to grasp the degree of effects that key input parameters used in the model would have on the output. Then, an optimum design condition for horizontal ground coupled heat pump system was suggested using several economic analysis tools. Economic analysis factors, such as internal rate of return, savings to investment ratio, and simple payback period, show that certain design conditions (coil pitch: 0.08 m, setting depth: 2.5 m, circulating fluid velocity: 0.7 m s −1 ) provide the most economic feasibility. However, this condition also varies with the unit cost of operation and initial investment.